IMPLEMENTASI GOOD GOVERNANCE DALAM OTONOMI DAERAH - Ade Permatasari (FISIP UMY, 2015)
implementation in localgovemment willgive positive side for the running of governance. Many aspects of good governance must be done to minimized local governance's weaknesses in the era of regional autonomy. Explanation of this a icle is stafted from the concept of Good governance ti the benefits that are obtained when good governance can be implemented.